What Makes Umbilical Cord Tissue-Derived Mesenchymal Stromal Cells Superior Immunomodulators When Compared to Bone Marrow Derived Mesenchymal Stromal Cells? - R. N. Bárcia; J. M. Santos; M. Filipe; M. Teixeira; J. P. Martins; J. Almeida; A. Água-Doce; S. C. P. Almeida; A. Varela; S. Pohl; K. E. J. Dittmar; S. Calado; et al. (Stem Cells International)
MSCs derived from the umbilical cord tissue, termed UCX, were investigated for their immunomodulatory properties and compared to bone marrow-derived MSCs (BM-MSCs), the gold-standard in immunotherapy. Immunogenicity and immunosuppression were assessed by mixed lymphocyte reactions, suppression of lymphocyte proliferation and induction of regulatory T cells. Results showed that UCX were less immunogenic and showed higher immunosuppression activity than BM-MSCs. Further, UCX did not need prior activation or priming to exert their immunomodulatory effects. This was further corroborated in vivo in a model of acute inflammation. To elucidate the potency differences observed between UCX and BM-MSCs, gene expression related to immune modulation was analysed in both cell types. Several gene expression profile differences were found between UCX and BM-MSCs, namely decreased expression of HLA-DRA, HO-1, IGFBP1, 4 and 6, ILR1, IL6R and PTGES and increased expression of CD200, CD273, CD274, IL1B, IL-8, LIF and TGFB2. The latter were confirmed at the protein expression level. Overall, these results show that UCX seem to be naturally more potent immunosuppressors and less immunogenic than BM-MSCs. We propose that these differences may be due to increased levels of immunomodulatory surface proteins such as CD200, CD273, CD274 and cytokines such as IL1β, IL-8, LIF and TGFβ2.